Effects of cation size on thermoelectricity of PEDOT:PSS/ionic liquid hybrid films for wearable thermoelectric generator application. Issue 36 (23rd August 2022) - Jiang, Kexing; Hong, Shao-Huan; Tung, Shih-Huang; Liu, Cheng-Liang
Abstract : The combination of PEDOT:PSS with four ionic liquids (XMIM BF4 ) having cations of various alkyl chain lengths and the same BF4 anion is studied to optimize the thermoelectricity. A prototype wearable thermoelectric generator is also established. Abstract : The conjugated polymer PEDOT:PSS and the related hybrid systems undoubtedly possess a high electrical conductivity and a reasonable Seebeck coefficient, showing potential for thermoelectric applications due to the feasibility of modulating their degree of doping by partially extracting the PSS section. Herein, the combination of PEDOT:PSS, with four ionic liquids (XMIM BF4 ) having cations of various alkyl chain lengths (methyl, ethyl, butyl, and hexyl denote X = M, E, B, and H, respectively) and the same tetrafluoroborate BF4 anion, was studied to optimize the thermoelectricity. It was found that the introduction of ionic liquids with small-(MMIM BF4 ) and large-sized cations (HMIM BF4 ) into the PEDOT:PSS film contributes to an improved Seebeck coefficient and conductivity, respectively. The obtained PEDOT:PSS/MMIM BF4 hybrids display a remarkably enhanced thermoelectric performance with the highest power factor of 86.3 μW m −1 K −2 measured at 313 K. The maximum output power of the robust 7-leg thermoelectric module reaches 10.4 nW for a temperature gradient of 14.0 K. It also exhibits excellent environmental stability with less than 10% variation in resistance for 28 days at room temperature without encapsulation and excellent mechanical flexibility under 500 bending cycles, respectively. A prototype wearable thermoelectric generator installed on the human wrist generates a thermovoltage of ∼0.74 mV with a 4.3 K temperature difference relative to the colder surroundings. Our finding highlights the importance of the rational selection of ionic liquids for enhancing the thermoelectric properties of a PEDOT:PSS film and indicates its potential for use in power generators.